REPRODUCTIVE PATTERNS OF HOLOTHURIA SCABRA (ECHINODERMATA: HOLOTHUROIDEA) IN INDONESIAN WATERS - Purwati, P. (Research Center for Oceanography - Indonesian Institute of Sciences (LIPI), 2006)
During 1993 to 1996, reproductive aspects of Holothuria scabra, one of the commercially important holothurian species in Indonesian waters were studied, which involved populations of Ambon Bay (eastern Indonesian waters), Saugi Island (central Indonesian waters) and Lampung Bay (western Indonesian waters). Those studies were reviewed in this paper, not only to reveal general patterns of reproductive seasons of populations throughout Indonesian waters, but also to provide more knowledge on gonadaltubule-development that has been rarely investigated on Indonesian holothurians. The review showed that the development of gonadal tubules amongst populations of Indonesian H. scabra were similar. Those included that: tubules across a gonad grew for one single reproductive cycle, and each tubule had equal opportunity to release their gametes in the same spawning event. These features conformed to general characteristics of this species throughout the world, and were different from the proposed tubule recruitment model of Smiley (1988). Each observed population showed fluctuation on gonad index, and individuals with fecund and/or post spawning gonads were recorded in most sampling occasions, resulting in fluctuation of gonad index. This attribute gave clue to through-year spawning activity with more intense during one or two periods in a year.